Intradiploic epidermoid cyst with large osteolytic lesions of the skull vault treated surgically: Lifelong implications - Mehdi Borni; Ahmed Maatoug; Fatma Kolsi; Mohamed Zaher Boudawar (Interdisciplinary Neurosurgery, 2020)
The epidermoid cyst (EC) is a rare benign tumor at the level of the vault which can reach unusually large dimensions and present an endocranial extension.The authors report the case of 44-year-old caucasian woman with intradiploic epidermoid cyst of the parietal bone with extracranial and intracranial extension and without neurological signs. The diagnosis was suspected on radiological imaging data and confirmed by pathological examination. Total excision of the cyst and its capsule followed by cranioplasty were performed. Postoperatively, the patient was discharged free of symptoms.